Human fatigue risk management : improving safety in the chemical processing industry - Murray, Susan L.; Thimgan, Matthew S.; ScienceDirect eBooks (London, UK : Academic Press is an imprint of Elsevier, 2016)
Human Fatigue Risk Management: Improving Safety in the Chemical Processing Industry teaches users everything they need to know to mitigate the risk of fatigued workers in a plant or refinery. As human fatigue has been directly linked to several major disasters, the book explores the API RP 755 guidelines that were released to reduce these types of incidents. This book will help users follow API RP 755 and/or implement a fatigue risk management system in their organization. Susan Murray, a recognized expert in the field of sleep deprivation and its relation to high hazard industries, has written this book to be useful for HSE managers, plant and project managers, occupational safety professionals, and engineers and managers in the chemical processing industry. As scheduling of shifts is an important factor in reducing fatigue and accident rates, users will learn the benefits of more frequent staff rotation and how to implement an ideal scheduling plan. The book goes beyond API RP 755, offering more detailed understanding of why certain measures for managing fatigue are beneficial to a company, including examples of how theory can be put into practice. It is a simple, digestible book for managers who are interested in addressing human factor issues at their workplace in order to raise safety standards.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed July 8, 2016).
Includes bibliographical references and index.
Elsevier
Safari Books Online
Keywords: Fatigue; Fatigue -- Prevention; Chemical industry -- Accidents -- Prevention; Chemical industry -- Accidents -- Prevention; Fatigue; Fatigue -- Prevention; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Electronic books